Estimativa da transpiração em meloeiro utilizando sensores de fluxo de seiva por dissipação térmica - Izídio, Naiara Sâmia de Caldas (Universidade Federal Rural do Semi-Árido, 2013)
The fluid requirements of crop plants are always an object of studies, to assist the performance evaluation of methods for estimating crop evapotranspiration (ETc). Therefore, this study aimed to estimate transpiration of muskmelon through the sap flow determined by thermal dissipation.The work was carried from August 2012 to July 2013 in two steps, the first stage consists of the construction and calibrating in different sap flow sensors for thermal dissipation (SFSD) small dimension order to be plants utilized in with small diameter as vegetable crops, to which was performed at the Laboratory of Instrumentation and Management in Irrigated Agriculture of the Federal Rural University of the Semi-Arid (UFERSA), Natal, RN.The second stage consistedof an experiment carried out under greenhouse located in the Department of Environmental Sciences and Technology - DCAT also belonging to UFERSA. The experimental design used was completely randomized blocks consisting of five treatments and three replications, totaling 15 parcels evaluated with sensorsconstructed by five different sizes of dissipators wires, the treatments being 1, 2, 3, 4 and 5dissipators with a length of wires of the Sensors 12, 15, 18, 21 and 24 cm, respectively.The data were analyzed by analysis of variance, utilizing the "R" software, averages between treatments were were compared by Tukey test at 5% significance. The results showed that the constructed and calibrated for vegetable crops plants sensors can be used to determine the flow of sap. The equations obtained for each sensor serve to to relate the sap flow temperature differences.TheSweating measure for the melon cantaloupe "Harper" with SFSD, of sizes 12 cm; 15 cm; 18 cm and 24 cm were obtained similar values of crop evapotranspiration
Estimation of transpiration in muskmelon utilizing sap flow sensors by thermal dissipation
Keywords: Cucumis melo L; Evapotranspiration; Temperature probes; Irrigation management; Cucumis melo L.; Evapotranspiração; Sondas de temperatura; Manejo de irrigação; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM